The Effectiveness of Teaching Reading Using the Needham Model in Improving the Reflective Thinking Skills of Tenth Grade Students in Jordan - Altarawneh, Dr. Zeyad Saleh Abdallah; Khasawneh, Dr. Mohamad Ahmad Saleem (Migration Letters, 2023)
The research aimed to determine if tenth-grade teachers who were using the Needham approach had improved their reflective thinking skills (visual vision, detection of fallacies, reaching conclusions, giving convincing explanations, and developing proposed solutions). Also, Analyzing the Needham model’s effectiveness after a month of involvement in terms of helping students with their reflective thinking. The study used a quasi-experimental design, including pre-post-follow-up assessments, to accomplish the objectives. 28 teachers of 10th grade were selected for the study’s sample in a practical way. Data comparing pre- and post-Needham model assessments of reflective thinking skills (visual vision, detection of fallacies, reaching conclusions, giving convincing explanations, and developing proposed solutions) showed statistically significant improvements for the post-test. Furthermore, there are no statistically significant changes in reflective thinking abilities between the post-and follow-up -tests.